Investigation Of Material Properties Of Sintered Black Point-1 Lunar Regolith Simulant - Ogunyinka, Adebayo Olutumbi (Department of Electrical Engineering, 2020)
The quest for establishing a human presence and development beyond the Earth, especially on the moon has opened up opportunities for future plans for lunar bases and settlements. However, the cost of using resources outside the lunar environment can inhibit this form of expansion, therefore the need for In Situ Resource Utilization (ISRU). The aim of this research was to investigate the possible usage of in situ resources for lunar construction and other economic development. The study evaluated different methods of material preparation using lunar regolith simulant for structural applications on the moon. The research employed the use of the regolith simulant known as Black Point-1 (BP-1). This research work presents the methodology used in developing lunar simulant and compares the properties of BP-1 regolith simulant to those of lunar soil, in terms of geotechnical and mechanical properties. Various laboratory analyses were carried out to determine these properties with the aid of thermal and analysis, particle size distribution, and XRD experiments. Our findings show that the particle size distribution and porosity of BP-1 are similar to that of the lunar regolith. The simulant was then sieved to produce four grades of powder (38 µmm, 106 µm, 212 µm and unsieved). The graded powders were then compressed to form a series of disc-shaped green compacts for sintering. The sintered samples were then subjected to compression testing. There were four different values of average compressive strength of the porosity materials ranging from lowest to highest porosity corresponding to the smallest to largest average grain sizes of 38 µm, 106 µm, unsieved and 212µm and they were 66.14MPa, 60.47MPa, 58.52MPa, 42.74 MPa, respectively. The particle size distribution was investigated on Black Point-1 simulant to determine the effect of the porosity while the bulk properties of the material were also examined for each of the four porosity grades, and this includes toughness, Poisson ratio, bulk modulus, Young’s modulus of elasticity and compressive strength. When compared with other ISRU structural materials and published data for real lunar regolith it was observed that sintered BP-1 is sufficiently strong for lunar structural applications.